Analisis Hukum Atas Standar Harga Satuan dan Analisis Standar Belanja Pemerintah Daerah: Implikasi terhadap Efisiensi, Transparansi, dan Potensi Sengketa Pengadaan di Kota Makassar - Irfan Syafar; Firmansyah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study examines the tendencies of the Unit Price Standard (SHS) and the Spending Standard Analysis (ASB), which are still positioned as budgetary administrative instruments. The method used is normative legal research with legislative, conceptual, and case approaches, based on various regulations on state finance, regional government, goods/services procurement, as well as the provisions of SHS and ASB in Makassar City. The data analysis technique is conducted prescriptively. The findings indicate that SHS and ASB perform dual functions: as instruments for budget planning and simultaneously as instruments of administrative law intended to prevent wasteful spending, mark-ups, and specification deviations. In the context of Makassar, the existence of Makassar Mayor Regulation Number 38 of 2024, Makassar Mayor Decree Number 1537 of 2025, and Makassar Mayor Regulation Number 22 of 2025 demonstrates the institutionalization of regulatory arrangements. Nevertheless, several issues remain, including regulatory fragmentation, limited methodological transparency, and the potential disharmony between regional price standards, market dynamics, and digital procurement instruments. This article proposes a normative strengthening model through the establishment of documented methodologies for determining SHS and ASB, integration with e-catalogues and market surveys, periodic updates, minimum data disclosure requirements, and measurable deviation mechanisms to reduce procurement disputes at the regional level